Core network service model and networking scheme oriented NB-IoT - Jiyan WANG; Xiaozhou WANG; Qian WU; Lili ZHU; Xiansu GAO; Yun LU; Mingming ZOU (Dianxin kexue)
It is a huge market space for narrowband-ineternet of things (NB-IoT),and NB-IoT is the focus of future development direction.The global telecommunications operators have begun to distributed actively.In order to better determine the network deployment of the construction program and resource allocation,from the business scene of NB-IoT,the NB-IoT service characteristics were analyzed,and the NB-IoT core network business model parameters and networking solutions were given,which was of great significance to the follow-up NB-IoT core network resource allocation and planning scheme.